Processes for coating surfaces with a copolymer made from sulfur and dicyclopentadiene. Issue 10 (14th December 2021) - Mann, Maximilian; Zhang, Bowen; Tonkin, Samuel J.; Gibson, Christopher T.; Jia, Zhongfan; Hasell, Tom; Chalker, Justin M.
Abstract : A copolymer made from sulfur and dicyclopentadiene was useful as a mercury sorbent, and also as a protective and repairable coating. Abstract : The reaction between sulfur and dicyclopentadiene was optimised to form a shelf stable and soluble low molecular weight oligomer. After a simple curing process at 140 °C the material was rendered insoluble and resistant to acids and solvents. Taking advantage of the soluble oligomer, silica gel was coated with the soluble oligomer and validated in mercury removal applications. The coating technique was also applied to metal, concrete, and polyvinyl chloride to illustrate broad protection from corrosion and solvents. The coating was also repairable, with surface scratches removed through the application of heat. In this way, the coating is active in metal binding, protective against acids and solvents, and repairable when damaged.